Adam Smith’s concept of labour: value or measure? - Rodríguez Herrera, Adolfo (2016)
Smith is considered the father of the labour theory of value developed by David Ricardo and Karl Marx and simultaneously of the cost-of-production theory of value developed by John Stuart Mill and Alfred Marshall. This polysemy is partly because Smith is developping the terminology to refer to value and measure of value, and often uses it with much imprecision. That has led to different interpretations about his position on these issues, most of them derived from an error of interpretation of Ricardo and Marx. This paper reviews the concepts developed by Smith to formulate his theory of value (value, real price and exchangeable value). Our interpretation of his texts on value does not coincide with what has traditionally been done. According to our interpretation, it would not be correct the criticism made by Ricardo and Marx on Smith’s position about the role of labour as measure of value. For these authors, Smith is not consistent in proposing that the value of a commodity is defined or measured as the amount of labour necessary to produce it and simultaneously as the amount of labour that can be purchased by this commodity. We try to show that for Smith the labour has a double role –as source and measure of value–, and that to it is due the confusion that generates his use of some terms: Smith proposes labour as a measure of value because he conceives it as a source of value. With this interpretation it becomes clear, paradoxically, that Smith holds a labour theory of value that substantially corresponds to the one later developed by Ricardo and Marx.